U.S. trade in the sphere of strategic products and services as the first level of analysis of its economic security - Todorović, Marina (Industrija, 2024)
The purpose of this research paper is to highlight the importance of the interplay between trade and economic performance, along with the connections among U.S. trade in critical goods and services and its economic security. The scientific paper seeks to elucidate why U.S. trade in strategic goods and services constitutes the primary axis of analysis for its economic security and explore the historical emergence of the concept of economic security. The realm of economic security is largely shaped by the economic policies and foreign trade actions taken by a country. The paper points out that the U.S. foreign trade policy model is among the most sophisticated in the world, if not the most detailed. New findings indicate that three major trends are fundamentally shaping economic security policies — resilience, protection and competition. Strategic competition with China is a cornerstone of U.S. economic security policy. The obtained insights indicate an in-depth examination of the wide range of U.S. foreign economic policy challenges and factors essential to developing strategies for competing with China. Methods used during the research are — the analytical-synthetic method, method of generalization and concretization, method of classification and, also, the historical method and content analysis method.
Keywords: U.S. trade, strategic goods and services, economic security, China